PERBEDAAN MORDAN ASAM JAWA (Tamarindus Indica Linn) DAN JERUK PURUT (Citrus Histrix) TERHADAP HASIL PENCELUPAN EKSTRAK BUAH SENDUDUK ( Melastoma Candidium D. Don) PADA BAHAN SUTRA - Andriani, Rika; Adriani, Adriani; Novrita, Sri Zulfia (Journal of Home Economics and Tourism, 2016)
The background of this research as an effort of finding new colors in the use ofnatural dyes for the textile industry. This study aims to reveal the color (hue ) ,dark-light color ( value) , the flatness of color and light and dark color differenceand color flatness of the difference mordant Tamarind and Kaffir Lime. Thisstudy was an experimental study. This type of data is a primary data sourced fromthe 15 panelists. The object is a silk cloth dipped with fruit extracts Sendudukwith mordant Tamarind and Kaffir Lime. Where the data analysis done by teknikanalysis of varianceone (one-way ANOVA). From the results of dyeing withoutmordant produce color Dark Purple # 5C4150, light dark color (value) is in thecategory of less bright and less flatness of color on the category average. Whilethe dyeing with mordant Tamarind generate color Red Violet # 7F4861 Popstardark light color (value) is in the category is quite bright and flatness of prettycolors on the category average. And dyeing with mordant Kaffir Lime generatecolor Red Violet # 904F6C Popstar dark light color (value) are in the category ofvery bright and flatness of color on the category average. The results ofhypothesis testing data obtained from the results showed differences in light anddark color ( value) ) with F count > F table = 38 176 > 3:22 Then Ho is rejected ,meaning that there are significant differences . As for the color flatness flatnessresults showed differences in color . The data obtained is F count > Ftable =10,280 > 3:22 Then Ho is rejected , meaning that there are significant differencesKata Kunci : Perbedaan Mordan, Ekstrak Buah Senduduk